IMPACT OF ACADEMIC AND HEALTH PROFESSIONALÂ€™S TRAINING IN THE PRACTICE OF PHYTOTHERAPY (CIPEEX, 2022)
THE INSERTION OF PHYTOTHERAPY IN THE HEALTH CARE NETWORK IS ONE OF THE ATTRIBUTIONS OF THE UNIFIED HEALTH SYSTEM (SUS). THE STRUCTURING AND THE STRENGTHENING OF THE NATIONAL POLICY ON MEDICINAL PLANTS AND PHYTOTHERAPEUTICS (PNPMF) GUARANTEES TO THE BRAZILIAN POPULATION SAFE ACCESS TO MEDICINAL PLANTS THAT HISTORICALLY BELONGS TO THE POPULAR HEALTHCARE REPERTOIRE. NONETHELESS, THERE ARE CHALLENGES BOTH IN TECHNICAL-SCIENTIFIC TRAINING AND IN THE TRAINING OF HEALTH PROFESSIONALS WORKING IN SUS. THIS WORK AIMS TO EVALUATE THE CONTRIBUTION OF THE COURSE €ŒMEDICINAL PLANTS AND PHYTOTHERAPY€ IN THE PROFESSIONAL PRACTICE IN PHYTOTHERAPY TO ANAPOLIS€™ PRIMARY HEALTHCARE PROFESSIONALS WHO JOINED THE COURSE AND AIMS TO ANALYZE THE APPLICATION OF THE METHOD MASSIVE OPEN ONLINE COURSE (MOOC) FOR EVANGELICAL UNIVERSITY OF GOIAS€™ HEALTH STUDENTS IN THE PILOT EDITION OF THE COURSE €ŒMEDICINAL PLANTS AND PHYTOTHERAPY€. THE RESEARCH WILL BE QUANTITATIVE-QUALITATIVE, EXPLORATORY AND DESCRIPTIVE. THE DATA WILL BE EXTRACTED FROM A QUESTIONNAIRE. THE COURSE WILL BEGIN IN NOVEMBER 2022 THROUGH THE EAD FREE COURSE PLATFORM OF THE EVANGELICAL UNIVERSITY OF GOIAS. THE RESEARCH WAS APPROVED BY THE ETHICAL RESEARCH COMMITTEE (Nº 5.182.052), ACCORDING TO RESOLUTION 466 FROM THE NATIONAL HEALTH COUNCIL. THE COURSE HAS THE SUPPORT AND PARTNERSHIP OF ANAPOLIS€™ HEALTH DEPARTMENT. FROM EXPECTED RESULTS IT IS HOPED THAT THIS WORK CAN CONTRIBUTE PROVIDING SUBSIDIES TO THE IMPROVEMENT OF INTEGRATIVE AND COMPLEMENTARY PRACTICES IN HEALTH€™S TEACHING, TO THE KNOWLEDGE OF THE USE OF MEDICINAL PLANTS AND NATIVE PLANTS FROM CERRADO.
Keywords: phytotherapeutic drugs; herbal medicine; learning; unified health system